2009
DOI: 10.2214/ajr.08.1753
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted MRI of Peritoneal Tumors: Comparison With Conventional MRI and Surgical and Histopathologic Findings—A Feasibility Study

Abstract: Adding DWI to routine MRI improves the sensitivity and specificity for depicting peritoneal metastases. Breath-hold DWI is now routinely used in all oncology patients referred for abdominal MRI at our institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(106 citation statements)
references
References 36 publications
1
103
0
2
Order By: Relevance
“…Diagnostic imaging is used to determine the suitability of the patient for surgery by assessing the primary tumor or by describing the disease volume and extent (7,8). DWI, as a functional MRI technique, provides non-invasive and high-resolution information on tissue characteristics based on molecular water diffusion properties, and the imaging output is useful to determine tissue microstructure, density, microcirculation and cellular organization (9,11,33). Several studies describe a close association between cell density and ADC values (16,(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnostic imaging is used to determine the suitability of the patient for surgery by assessing the primary tumor or by describing the disease volume and extent (7,8). DWI, as a functional MRI technique, provides non-invasive and high-resolution information on tissue characteristics based on molecular water diffusion properties, and the imaging output is useful to determine tissue microstructure, density, microcirculation and cellular organization (9,11,33). Several studies describe a close association between cell density and ADC values (16,(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion weighted imaging (DWI) is a non-invasive technique based on molecular water diffusion properties, and may be used to characterize tissue architecture based on microstructure, cellular density, microcirculation and cell organization (9)(10)(11). DWI has been demonstrated to be more accurate compared with computed tomography (CT) for characterizing the sites of implants of ovarian cancers, including metastases to the liver, lungs, kidneys, uterus and pancreas (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Fujii et al [47] showed sensitivity and specificity of 90% and 95.5% respectively for diffusion weighted imaging in detecting such deposits. In another study done by Low et al [48] combined conventional and DWI imaging showed better sensitivity and accuracy than DWI alone …”
Section: Peritoneal Depositsmentioning
confidence: 92%
“…When combined with conventional MRI, DWI has been shown to increase the sensitivity(90 %) and specificity( 95.5 %) [24] Site specific disease, particularly small deposits in mesentery, serosa of bowel, peri-hepatic and peri-pancreatic areas are better evaluated by DWI MRI [25] (Fig. 2).…”
Section: Diffusion Weighted Mri (Dwi)mentioning
confidence: 99%
“…These lesions can be demonstrated by both CT and DWI MRI. [25] Pelvis The uterus, bladder and rectum are partially covered by the peritoneum. The recto vesical space in males and the rectovaginal space in females form the most dependent portions of the pelvic cavity and therefore are frequent sites of metastatic disease.…”
Section: Para Colic Guttersmentioning
confidence: 99%